Role of survivin expression in predicting biochemical recurrence after radical prostatectomy: a multi‐institutional study. (5th April 2016) - Mathieu, Romain; Lucca, Ilaria; Vartolomei, Mihai D.; Mbeutcha, Aurélie; Klatte, Tobias; Seitz, Christian; Karakiewicz, Pierre I.; Fajkovic, Harun; Sun, Maxine; Lotan, Yair; Montorsi, Francesco; Briganti, Alberto; et al.
Abstract : Objective: To assess the association of survivin expression with clinicopathological features and biochemical recurrence (BCR) after radical prostatectomy (RP) in a large multi‐institutional cohort. Methods: Survivin expression was evaluated by immunohistochemistry on a tissue microarray of RP cores from 3 117 patients. Survivin expression was considered altered when at least 10% of the tumour cells stained positive. The association of altered survivin expression with BCR was evaluated using Cox proportional hazards regression models. Results: Survivin expression was altered in 1 330 patients (42.6%). Altered expression was associated with higher Gleason score on RP ( P = 0.001), extracapsular extension ( P = 0.019), seminal vesicle invasion ( P < 0.001) and lymph node metastases ( P = 0.009). The median (interquartile range) follow‐up was 38 (21–66) months. Patients with altered survivin expression had a shorter BCR‐free survival time than those with normal expression (5‐year BCR‐free survival estimates: 74.7 vs 79.0%; P = 0.008). Altered survivin expression did not retain its prognostic value, however, after adjustment for the effect of established clinicopathological factors ( P = 0.73). Subgroup analyses also showed no independent prognostic value of survivin. Conclusions: Survivin expression is commonly altered in patients undergoing RP. Altered survivin expression is associated with the clinicopathological features of biologically and clinically aggressive PCa. Survivin expression was associated with BCR only in univariable analysis, limiting its value in daily clinical decision‐making.